2016
DOI: 10.1002/ange.201604833
|View full text |Cite
|
Sign up to set email alerts
|

The Strong Influence of Structure Polymorphism on the Conductivity of Peptide Fibrils

Abstract: Peptide fibril nanostructures have been advocated as components of future biotechnology and nanotechnology devices. However, the ability to exploit the fibril functionality for applications, such as catalysis or electron transfer, depends on the formation of well‐defined architectures. Fibrils made of peptides substituted with aromatic groups are described presenting efficient electron delocalization. Peptide self‐assembly under various conditions produced polymorphic fibril products presenting distinctly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The details of gelation of NMI-GW-OMe is given in Table 1. Recently, several emerging properties 26,[36][37][38][39][40][41][42][43] of planar fluorophores have been observed in mixed solvents. One of them is supramolecular gelation [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] .…”
Section: Resultsmentioning
confidence: 99%
“…The details of gelation of NMI-GW-OMe is given in Table 1. Recently, several emerging properties 26,[36][37][38][39][40][41][42][43] of planar fluorophores have been observed in mixed solvents. One of them is supramolecular gelation [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] .…”
Section: Resultsmentioning
confidence: 99%
“…Short peptides with the sequence of the core recognition motif (or similar sequences) can both inhibit the fibrillization process, as well as forming similar amyloid‐like structures by themselves . In recent years, Ashkenasy and co‐workers have used these short peptides as well as other fibril‐forming short peptides to increase the conduction across amyloid‐like fibrils . The main advantage of using short peptide sequences is the relative ease of chemical modifications in terms of amino acids and sequence changes.…”
Section: Biomolecular Electronic Materials At the Macroscalementioning
confidence: 99%
“…Another group of fibril‐forming peptides that belong to the short peptide family but bear no resemblance to amyloid proteins/peptides in terms of the amino acid sequence are termed amyloid‐like structures. Several amyloid‐like structures which can self‐assemble from diverse peptide building blocks have been studied for their electrical conductance properties ( Figure ) . Ashkenasy and co‐workers have shown that both electrostatic and aromatic interactions can induce the fibrillization of (FKFE) 2 peptides to thin (3–5 nm) fibrils in water.…”
Section: Biomolecular Electronic Materials At the Macroscalementioning
confidence: 99%
See 2 more Smart Citations